Bone height and width evaluation before dental implant placement on panoramic radiographs: a scoping review - Shely Levita Asmarani; Azhari Azhari; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: The aim of this study is to evaluate the bone height and its width on panoramic radiography prior to dental implant placement. Review: This study was carried out using scoping review methods. The referenced articles were published between 2010-2021 in English or Indonesian. The search was performed using PubMed and PMC database with keywords “(((Evaluation) AND (Presurgical)) AND (Dental Implant)) AND (Radiograph)) AND (Panoramic)” and Science Direct with keywords